Management Control, Collaboration Behaviour and Fresh Produce Supply Chain Performance in Weifang Area, China - Fengzhao, Yin (Faculty of Economics and Business, 2025)
Fresh produce supply chains (FPSCs) face significant challenges in management and control, particularly in emerging markets like China. These challenges include complex stakeholder relationships and the lack of empirical evidence on how management practices and collaboration behaviour interact to influence supply chain performance. Although existing research has examined individual aspects of supply chain management, there remains a limited understanding of the integrated effects of management control practices and collaboration behaviour on FPSC performance.